A Novel Technique to Utilize Second Waste of Plastic Bottle as Soil Reinforcement: A Comparative Study on Mechanical Properties with Natural Black Cotton Soil - Tezeta Moges Adane; Alemgena Alene Araya; B. Karthikeyan; Senthil Kumaran Selvaraj; S. Jose; A. John Rajan; D. Vincent Herald Wilson (Advances in Civil Engineering)
Black cotton soils, which are expansive, are present in abundance in Ethiopia. This type of soil possesses expansion when saturated with water and contraction during hot seasons, due to which it is labelled as “weak soil.” They may remain a threat to the structures if they are constructed over them without precautions. The quality of such soils can be improved by treating them with suitable stabilizers or soil reinforcers. This paper discusses the chances of using the second waste of plastic bottles as a reinforcer to strengthen weak black cotton soils in Ethiopia. Second, plastic bottle waste was added at 1%, 2%, 3%, 5%, 7%, and 9% to the soil, and numerous trials were conducted to ensure the reliability of the results. The effects were analyzed based on the results from the Atterberg limit tests, compaction tests, unconfined compression strength (UCS) tests, and the California bearing ratio test (CBR) for soaked and unsoaked conditions. The results were compared against the natural soil results, and the optimum usage percentage of second waste plastic required to reinforce the soil was reported. The results indicate that among the various properties used, the mix with 2% second waste plastic is effective with numerous trials being conducted to ensure the reliability of the results and decreased values of OMC by 18.5%, increased MDD by 1.9%, increased CBR by 50.9%, and increased UCS by 10.1%. Thus, the research provides a novel technique to recycle plastic waste once again as soil reinforcement, thereby saving the environment from dumped waste.